Integrating Next Generation Science Standards Dimensions in Preparing Prospective Biology Teachers Oriented to Traditional Food Culture - Ika Sukmawati; Ayu Rahayu; Muhammad Radian Nur Alamsyah (Yayasan Keluarga Guru Mandiri, 2026)
This study examines the declining interest among prospective biology teachers in traditional food culture, which is essential to supporting sustainable development goals, particularly food security and environmental sustainability. The research aims to develop a learning model integrating the Next Generation Science Standards (NGSS) dimensions with traditional food culture, known as the Traditional Food Culture Learning (TFCL) model. A research and development (RD) method based on the Dick and Carey instructional design was employed, involving prospective biology teachers at Universitas Tidar. The model was developed through stages of needs analysis, design, validation by multidisciplinary experts, and revision. The results indicate that the TFCL model is feasible and effective, with validation scores indicating very strong performance. The model's implementation shows significant positive relationships among exploration of local knowledge, nutritional analysis skills, and student engagement. The study concludes that the TFCL model enhances teaching competencies and fosters awareness of traditional food culture. This research contributes to science education by providing an innovative, culturally contextualized learning model that integrates global standards with local wisdom to promote sustainability-oriented learning.